Two Postpartum Blood Collection Devices: The Brass-V Drape and MaternaWell Tray-As Experienced by Birth Attendants and Birthing Women-A Questionnaire-Based Randomised Study - Jade Esau; Timothy Morris; Chris Muller; Christine Els; Liesl de Waard (Hindawi Limited, 2024)
Background. Postpartum haemorrhage is the leading cause of preventable maternal mortality worldwide. Early identification and prompt management of postpartum haemorrhage improve outcomes. Objective assessment of postpartum blood loss is an important step in identifying postpartum haemorrhage. The Brass-V drape and MaternaWell tray have been designed for routine measurement of postpartum blood loss. The perceived utility and acceptability of these devices to the parturients and birth attendants still begged exploring. Objective. To assess the perceived usefulness and ease of use of a Brass-V drape versus a MaternaWell tray for the collection of postpartum blood loss. Methods. We conducted a prospective parallel randomised trial, employing a questionnaire to assess the experiences of birth attendants and birthing women who used these devices. The study was conducted at site B midwife obstetric unit in Khayelitsha Cape Town. Pregnant women presenting in early labour were approached for voluntary participation. After informed consent was obtained, participants were randomly assigned to the Brass-V drape or the MaternaWell tray, which the birth attendant placed after the birth of the baby. Results. There were 63 participants, of which 33 were assigned to the MaternaWell tray and 30 to the Brass-V drape. Birth attendants indicated a desire to use the MaternaWell tray (30 (90%)) or Brass-V drape (26 (87%)) in future deliveries. The parturients were also in favour of the future use of MaternaWell tray (33 (100%)) and Brass-V drape (28 (93%)). Ease of measurement favoured the Brass V-drape, and ease of placement favoured the MaternaWell tray. Five (8%) participants experienced postpartum haemorrhage, two with the MaternaWell tray and three with the Brass-V drape. One parturient required hospital transfer. Conclusion. The responses of the birth attendants and parturients were positive. The MaternaWell tray has the benefit of reuse and lower cost and is an acceptable alternative to the Brass-V drape. Both devices aid in the early recognition of postpartum haemorrhage.